MODEL PELATIHAN UNTUK MENINGKATKAN KOMPETENSI CALON KONSELOR MULTIKULTURAL - Herdi Herdi (Jurnal Ilmiah Visi, 2012)
The purpose of this study is to produce a hypothetical training model to improve the competence of multicultural counselor candidates. The research was conducted at Guidance and Counseling Department, School of Education, State University of Jakarta as from March through December 2012. The samples were selected from the nonregular program students of 2009 attending Social-Cultural Study Course. Employing Research and Development Mode, the data were collected by using KKM instruments for counselor candidates which had been validated. The model produced from this research consists of frame work component, training phases, training format, training curriculum (content, method, process), training norm, counselor educator’s role, and training evaluation. The research recommends to do do further research to evaluate the effectiveness of the model.